2018
DOI: 10.7150/ijms.23054
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Expression of A Venous Malformation Related Mutation, TIE2-R849W, Significantly Induces Multiple Malformations of Zebrafish

Abstract: A TIE2 mutation causing arginine-to-tryptophan substitution at residue 849 (TIE2-R849W) is commonly identified in heredofamilial venous malformation. However, there is no in vivo model to confirm the pathogenic role of TIE2-R849W. Humanized TIE2-R849W plasmid was constructed via PCR-mediated site-directed mutagenesis. After transcription and micro-injection, TIE2-R849W significantly induces multiple malformations in zebrafish: caudal vein plexus (CVP) defect, eye abnormalities, forebrain formation perturbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Adobe Photoshop 7.0 software (Adobe, San Jose, CA, USA) was used to adjust the level, brightness, contrast, hue, and saturation of a series of images to optimize the visual representation. 23 …”
Section: Methodsmentioning
confidence: 99%
“…Adobe Photoshop 7.0 software (Adobe, San Jose, CA, USA) was used to adjust the level, brightness, contrast, hue, and saturation of a series of images to optimize the visual representation. 23 …”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, multiple malformations such as head malformations, which fall into the phenotypic spectrum of human PROS, have been observed in zebrafish injected with the most common GOF TIE2 mutant ( R849W ). Vascular defects in caudal vein plexus formation in these zebrafish mirrors human VeMs,121 demonstrating similar vascular phenotypes in humans and zebrafish through VeMs-causative mutant forms of TIE2 . Since tie2 is located upstream of the PI3K/AKT/mTOR pathway, which plays a crucial role in the pathogenesis of VeMs, zebrafish were then injected with a constitutively active form of human myrAkt1, resulting in observations of wide-spread malformations, including skin hyperplasia/hypertrophy, also within the phenotype spectrum of human PROS 122.…”
Section: Introductionmentioning
confidence: 69%
“…Finally, the disappearance of DLAV formation was also observed in zebrafish injected with GOF MAP3K3 mutation (I441M) mRNA at ~48 hpf,4 suggesting that MAP3K3 is downstream of VEGFR in the PI3K/AKT/mTOR signalling cascade and plays an inhibitory role in embryonic artery development. Phenotypic differences in angiogenic events in zebrafish indicated that CCM signalling complex-mediated signalling does not intersect with the enhancement of RTKs (VEGFR, TIE2)/PI3K/AKT/mTOR signalling cascades 4 121 122…”
Section: Introductionmentioning
confidence: 99%
“…Wnt plays a critical role in zebrafish craniofacial patterning, as well as tooth and bone development. Abnormal expression of related molecules in the signaling pathways may lead to craniofacial malformations, including significant eye defects and mandibular deformities (Du, Ma, Zhang, Zheng, & Wang, 2018; Nakamura et al, 2007; van de Water et al, 2001). Inhibition of wisp3 (WNT‐1 inducible signaling pathway protein 3) protein expression affects the size and shape of the pharyngeal cartilage of zebrafish (Nakamura et al, 2007).…”
Section: Craniomaxillofacial Developmental Disorders Of Zebrafishmentioning
confidence: 99%
“…Wnt plays a critical role in zebrafish craniofacial patterning, as well as tooth and bone development. Abnormal expression of related molecules in the signaling pathways may lead to craniofacial malformations, including significant eye defects and mandibular deformities (Du, Ma, Zhang, Zheng, & Wang, 2018;Nakamura et al, 2007;van de Water et al, 2001).…”
Section: Genetic Factors Contributing To Jaw Developmental Deformitymentioning
confidence: 99%